Prática profissional do assistente social em um complexo psiquiátrico: religião, religiosidade e espiritualidade no trato de pessoas com o espectro da esquizofrenia - Silveira, Nara Patrícia Mendes da (2020)
It approaches a research with social workers working in the field of mental health and addresses the importance of religion, religiosity and spirituality in recovery and support for coping with mental disorder. The purpose of this dissertation is to investigate how mental health professionals, social workers, deal with religion, religiosity and spirituality as a relevant tool in the treatment, strengthening and better mental health of patients. It was developed through a qualitative research effective by the methodology of analysis of the Collective Subject Discourse. It is organized into three chapters. The first approaches a contextualization about religion, religiosity and spirituality. Its philosophical assumptions and implications to the spectrum of schizophrenia. The third is research with social workers. It was carried out from three questions that revolve around religion, spirituality and religiosity and with treatment of the person with schizophrenia spectrum. It is concluded that for the field of religion, spirituality and religiosity in the treatment of people with mental disorders, caution and ethical prudence are necessary.